The The Effectiveness Of Service Quality, Price, And Customer Loyalty On Purchasing Decisions At The “Blue” Drinking Water Kiosk In The Temple Sub-District Of Sidoarjo District. - Mukhammad Aditya Firdaus; Detak Prapanca; Rizky Eka Febriansah (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
Water is a component of the atmosphere that must be protected to benefit human life and other living things. Everyone has different water needs, depending on where they live and the level of their needs. The goal of this study is to understand the correlation between customer loyalty, price, and service quality and the buying’s decisions at the “BIRU” drinking water kiosk in the temple sub-district of sidoarjo district. this research uses quantitative methods. The study used a population of drinking water consumers at the “BLUE” Candi kiosk. The study collected a sample of 100 individuals. In the study, questionnaires were distributed via Google Form. Research shows that service quality has a negative impact on purchasing decisions, but price and customer loyalty have a positive impact on purchasing decisions